(untitled) (AYUSHDHARA, 2024)
According to Ayurveda, face is viewed as a reflection of the body’s internal state. Mukha Twak Pariksha enable practitioners to assess facial skin’s condition- its texture, colour, and any abnormalities. This examination can uncover underlying imbalances or health issues affecting both the skin and internal organs. Aim and Objective: The aim of the study is to evaluate skin examination through Ayurvedic and basic contemporary parameters in Saundarya Ayurveda through classical approach and skin analysis with basic contemporary scales and Instruments. Method: The points related to face, skin and hair are extracted from classical texts and converted into a basic proforma for better analysis. A study of 100 subjects were conducted using the proforma for its outcome and analysis. A questionnaire was also developed with reference to “CCRAS Prakriti Assessment Manual of SOP’s”. Result: The analysis revealed prevalent dry skin, mild acne, and early wrinkles due to environmental dryness, while hair showed minimal scalp dryness and few split ends, reflecting good hair care. Conclusion: Both Ayurveda and contemporary skincare emphasize individualized care and holistic health, but differ in diagnostics, Ayurveda focuses on Dosha balance, while modern methods use advanced tools and external factors; integrating both could enhance personalized skin health strategies.